Nodular glomerulosclerosis in a non-diabetic hypertensive smoker with dyslipidemia - Falcão Pedrosa Costa, A.; Albert Gomes dos Santos, W.; Gonçalves Pontes Filho, M.A.; Teles Farias, F.; Modesto dos Santos, V. (Anales del Sistema Sanitario de Navarra, 2011)
Nodular glomerulosclerosis may be idiopathic or develop associated with diabetes mellitus, membranoprolipherative glomerulonephritis, light or heavy chain deposits, amyloidosis, fibrillary or immunotactoide disease, and Takayasu’s arteritis. Histological features of idiopathic nodular glomerulosclerosis are similar to the Kimmelstiel-Wilson changes. Recent evidence points to the role of hyperglycemia, hyperlipidemia, hypertension and smoking in the mechanisms of this uncommon condition. The case study of a 65-year-old male presenting recent arterial hypertension and nodular non-diabetic glomerulosclerosis is described, and the possible role of heavy smoking in the pathogenesis of this condition is emphasized.